Application of IoT technology in the prevention of geological hazard - Hui QIAO; Tao WANG; Zhiyuan XIE (物联网学报)
A system of on-line monitoring,warning,command and dispatch of geological hazard based on the IoT was presented,which was based on the practice of the China Mobile IoT Company on-line monitoring and warning project of geological hazard,and the preventing techniques of geological hazard at home and abroad.The system mainly consisted of four links:online automatic monitoring,geological disaster warning,command and decision-making,rescue scheduling.The system could monitor the geological hazards for 24 hours uninterruptedly,automatically finding the anomaly of the geological hazard points and alarm automatically when abnormal state of the hidden danger points was found.Through the intelligent data analysis,the system could help commanders make the scientific decision quickly; through the IoT label on the rescue personnel,equipment and materials,the system could show them on the map in real time to help commanders dispatch rescue forces to arrive at the scene as soon as possible.Finally,several key technology applications of geological hazard preventing system were prospected.